The representations of public teaching in the article “Rudimentary schools” of Manoel Dantas (Research, Society and Development, 2018)
In Rio Grande do Norte, during the first two decades of the twentieth century, the intellectual Manoel Dantas was at the head of the General Direction of Public Instruction. Due to his role as Director and Educator, he was invited by the Teachers' Association to draw up considerations on public teaching in Pedagogium Magazine. This study is inserted in the perspective of Cultural History, based on the notion of Representation, according to the sense given by the French historian Roger Chartier (2002). Thus, the objective is to analyze the representations of public education presented by Manoel Gomes de Medeiros Dantas in the article "Rudimentary Schools", published in 1921, in the Pedagogium Magazine. Finally, it is concluded that throughout the article, the author presents several aspects of the trajectory of public education in Rio Grande do Norte. Thus, it can be seen in the different political administrations that the common denominator was the concern, as regards the intellectual development of the population, through instruction, according to the reading of the representations contained in speech. The offered education improved with the construction of the school groups, and was spread, to the most inaccessible places of the State, with the installation of rudimentary schools. These schools meant an option that at a lower cost and in a shorter period of time could literate a greater number of people, besides giving access to the school to a higher percentage of students as it was possible to verify from the statistical data found in Manoel's Dantas article.